Unraveling the Importance of Nitrogen Nutrition for the Thermotolerance of Irrigated Crops: A Review - Francisco Sales Ferreira dos Santos Júnior; Aline Dell Passo Reis; Renato de Mello Prado (Horticulturae)
Climate change has intensified the increase in irrigated crops to solve frequent droughts, but part of the stress continues due to heat waves, and for these systems, there is a lack of in-depth discussion about their damage and strategies to minimize this damage. The damage caused by high temperatures may be exacerbated in crops with a nutritional disorder of nitrogen, but optimized management of this nutrient can help mitigate the effects of this stress. This merits further debate, as it would be a sustainable strategy without risk to the environment and at the same time could induce greater plant tolerance to heat stress. This review will address the relevance of rising temperatures and their isolated effects on crop nutrition and productivity and the role of optimized nitrogen use in mitigating this stress and propose future perspectives for this research that could help researchers improve thermotolerance. Nitrogen plays an essential role in plant metabolism, inducing the production of proteins from photosynthesis, boosting primary and secondary plant metabolism and, consequently, the production and defense systems of the plant. Studies indicate that adequate nitrogen supplementation can increase plant resilience to high temperatures, improving water use efficiency and promoting the synthesis of heat shock proteins. In addition, new strategies in nitrogen fertilizer management, such as the use of nitrification inhibitors and biofertilizers, have demonstrated greater efficiency in the use of nitrogen, reducing environmental losses, and, consequently, they could have an impact on stress mitigation. Although nitrogen can mitigate the negative effects of heat waves on plants, there are still gaps in the knowledge about the underlying biochemical and physiological mechanisms involved and whether the doses of N used in research are really optimal for maximizing the plant’s defense system against stress. The future outlook is that optimal N management will become important not only to guarantee high yields but also to minimize heat wave losses by strengthening the plant’s defense mechanisms to deal with this stress. In the context of climate change, a better understanding of the benefits of N will help to better manage heat stress towards more sustainable agriculture.